Bimetal carbon nanocube doped alginic acid hydrogel as well as preparation method and application thereof

By combining the carbonized Cu-Co-ZIF with sodium alginate, a bimetallic carbon nanocube-doped alginate hydrogel is prepared, which solves the problem of difficulty in removing organic pollutants such as azo dyes in water in the prior art, and achieves efficient Fenton reaction and sewage treatment effects.

CN119549197APending Publication Date: 2025-03-04QINGDAO UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411727746.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

The prior art is difficult to effectively remove organic pollutants such as azo dyes in water, and the MOF materials are unstable in the aqueous phase, making the powder shape difficult to recycle.

Method used

By combining the carbonized Cu-Co-ZIF with sodium alginate, a bimetallic carbon nanocube-doped alginate hydrogel was prepared and treated in a solidification bath of FeCl3 to form a porous structured hydrogel, which promoted the circulation of the Fenton reaction.

Benefits of technology

It significantly improves the performance of the Fenton reaction, can efficiently degrade a variety of pollutants, including azo dyes, and is stable in hydrogels, suitable for mass production and wastewater treatment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119549197A_ABST
    Figure CN119549197A_ABST
Patent Text Reader

Abstract

The invention discloses a bimetallic carbon nanocube doped alginic acid hydrogel and a preparation method thereof, Cu-Co carbon nanocubes are doped into sodium alginate, and the hydrogel is formed in a FeCl3 solution by utilizing a titration method. The hydrogel prepared by the method disclosed by the invention can efficiently degrade pollutants in water under the synergistic effect of the hydrogel and hydrogen peroxide under illumination, and has good stability and recoverability. Compared with the prior art, the preparation method provided by the invention has the characteristics of simple and easy-to-control process, low manufacturing cost, small environmental pollution and the like, can realize industrial production, and can be applied to the technical field of environment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of environmental technology, and specifically relates to a bimetallic carbon nanocube-doped alginate hydrogel and a preparation method and application thereof. Background Art

[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.

[0003] Today, we have more than 700,000 tons of commercial dyes and pigments every year, of which more than 5% are released into water as pollutants. Azo dyes, as the largest class of synthetic dyes, account for 70% of all known commercial dyes. Azo dyes are widely used in dyeing and printing processes of various fibers due to their advantages such as easy coloring and easy synthesis. However, the use of azo dyes also poses a huge threat to our living environment. Most azo dyes are toxic and contain one or more aromatic azo groups. They can have teratogenic, carcinogenic and mutagenic effects on the human body, and can cause human allergies, cancer and mutations.

[0004] Organic pollutants that cannot be naturally degraded have always been a difficult problem to solve in water treatment. Currently, methods for removing these organic pollutants include photocatalysis, adsorption, Fenton method and biological treatment. Advanced oxidation processes (AOPs) have the advantages of being the most effective, convenient and thorough in removing pollutants in water treatment. AOPs have been proven to be an excellent alternative for treating specific substances because they can reduce organic molecules to carbon dioxide, water and inert salts (mineralization).

[0005] Metal organic materials (MOF) are porous crystalline materials composed of metal ions or metal clusters coordinated with organic ligands, so they are also called porous coordination polymers. MOF materials are widely used in electrocatalysis, energy storage and other fields due to their excellent physical properties. They have good chemical stability, porosity, high specific surface area and the ability to stably load metals. However, MOF materials are very unstable in water phase, and powdered MOF materials are difficult to recycle.

[0006] The reaction of Co ions and dimethyl imidazolate can generate a cubic crystalline material with a stable structure, and the porous carbon material liquid after carbonization retains its cubic crystalline structure. However, it has been reported that Co ions act as a catalyst for the Fenton reaction. 3+ To Co 2 +The redox transformation of is the limiting step in the Fenton reaction. Previous reports have confirmed that Cu can significantly improve the Fenton-like activity in H2O2 activation by reducing the adsorption energy and promoting electron transfer. Copper can also be introduced into the cobalt-based heterogeneous Fenton system to prepare copper-cobalt-based Fenton catalysts with enhanced catalytic performance, which is mainly due to the synergistic effect of copper and cobalt in the catalytic reaction process.

[0007] Sodium alginate is a biopolysaccharide composed of β-D-mannuronic acid (M) units and α-L-guluronic acid (G) units. These G, M units in seaweed polysaccharides can form a stable eggshell structure by chelating with divalent or trivalent metal ions, because fibers or hydrogels can be prepared by injecting sodium alginate into a metal ion solution. Seaweed hydrogels are widely used in medical and protective fields due to their environmental friendliness, good absorption capacity and biocompatibility, but there are fewer studies on their use as functional materials in environmental remediation, especially sewage treatment. Therefore, the development of alginate hydrogels with a porous stable structure and sewage treatment function has important scientific significance and application value. Summary of the invention

[0008] In order to solve the above problems, the present invention provides a bimetallic carbon nanocube doped alginate hydrogel and its preparation method and application. The carbonized Cu-Co-ZIF is combined with sodium alginate, and then the hydrogel is prepared in a FeCl3 coagulation bath by titration. The addition of carbon nanocubes can not only increase the pore size and surface area of ​​the hydrogel, but also the addition of Cu and Co can participate in and promote the cycle of Fenton reaction, so that the Fenton performance is greatly improved, and it has good degradation performance for various pollutants, and can achieve mass production and be applied in the field of sewage treatment.

[0009] Specifically, the technical solution of the present invention is as follows:

[0010] In a first aspect of the present invention, a bimetallic carbon nanocube-doped alginate hydrogel is provided, wherein the alginate hydrogel comprises a sodium alginate skeleton, Cu-Co-carbon nanocubes distributed on the sodium alginate skeleton, and Fe-Co ... 3+ .

[0011] The second aspect of the present invention provides a method for preparing the above-mentioned bimetallic carbon nanocube-doped alginate hydrogel, comprising the following steps:

[0012] S1, carbonizing Cu-Co-ZIF to obtain Cu-Co-carbon nanocubes;

[0013] S2, add Cu-Co-carbon nanocubes to the sodium alginate aqueous solution, and add the mixture to the Fe-containing 3+ in a coagulation bath to obtain the product.

[0014] Preferably, in step S1, the specific preparation steps of the Cu-Co-ZIF are: adding an aqueous solution mixed with copper salt and cobalt salt to a dimethylimidazole aqueous solution, and the mixed solution is allowed to stand for reaction to obtain the Cu-Co-ZIF;

[0015] Wherein, the mass fraction of the dimethylimidazole aqueous solution is 0.07% to 0.08%; the molar ratio of the copper salt to the cobalt salt is 3 to 5:5 to 7, preferably 4:6;

[0016] The copper salt is selected from one or more of copper nitrate, copper sulfate and copper chloride, and the cobalt salt is selected from one or more of cobalt nitrate, cobalt sulfate and cobalt chloride; further preferably, the copper salt is copper nitrate, and the cobalt salt is cobalt nitrate;

[0017] The standing time is 12 to 16 hours; more preferably, the mixed solution after the standing reaction is centrifuged to obtain Cu-Co-ZIF.

[0018] Preferably, in step S1, the reaction conditions of the carbonization treatment are: in an inert environment, heating to 450-600°C at a heating rate of 1-3°C / min, and keeping warm for 1-3h; further preferably, heating to 600°C at a heating rate of 2°C / min, and keeping warm for 2h.

[0019] Preferably, in step S2, the sodium alginate is extracted from marine biomass resources, and the marine biomass resources are selected from one or more of brown algae, sargassum, and agar; further preferably, the mass concentration of the sodium alginate aqueous solution is 2.0% to 3.0%.

[0020] Preferably, in step S2, the sodium alginate aqueous solution is prepared by dissolving sodium alginate in deionized water, stirring the mixture to form a uniform sol, and then performing a vacuum degassing treatment.

[0021] Further preferably, the stirring reaction time is 1 to 3 hours, the temperature is 20°C to 30°C, and the stirring rate is 500 to 700 r / min; the temperature of the vacuum degassing treatment is 50 to 70°C, and the pressure is -20 to -30 KPa.

[0022] Preferably, in step S2, the mass ratio of the Cu-Co-carbon nanocubes to sodium alginate is 0.8-1.2:1.5-2.5; preferably 1:2.

[0023] Preferably, in step S2, the Fe-containing 3+The coagulation bath is an FeCl3 aqueous solution, the mass fraction of the FeCl3 aqueous solution is 4% to 6%, and the reaction time is 8 to 15 hours.

[0024] The third aspect of the present invention provides an application of bimetallic carbon nanocube-doped alginate hydrogel prepared by the above method in the field of sewage treatment;

[0025] Preferably, the organic pollutants in the sewage treatment include malachite green, rhodamine B, and tetracycline;

[0026] Further preferably, the method for degrading organic pollutants comprises: adding bimetallic carbon nanocube-doped alginate hydrogel to wastewater containing organic pollutants, adjusting the pH to 3-7, and after the hydrogel is completely dispersed and adsorption equilibrium is reached, photocatalytically degrading the organic pollutants with hydrogen peroxide under visible light.

[0027] One or more embodiments of the present invention have at least the following beneficial effects:

[0028] (1) The hydrogel prepared by the present invention has a porous morphology, which provides more reaction sites compared to the smooth surface of alginate hydrogel, making it easier for organic pollutant molecules to combine with the reaction sites in the hydrogel, thereby improving the reaction efficiency.

[0029] (2) The hydrogel prepared by the present invention has Fenton properties. After adding Cu-Co-carbon nanocubes (Cu-Co-CNC), the degradation performance of the prepared hydrogel for azo dyes is greatly improved, and the degradation rate of malachite green can reach 90% within 80 minutes. This is due to the porous morphology after the addition of Cu-Co-CNC and the promotion and participation of Cu and Co in the Fenton cycle.

[0030] (3) The carboxyl groups in the alginic acid of the present invention can react with Fe 3+ Coordination, the ligand and Fe 3+ Stable complexes are formed to minimize the photo-Fenton process. Under UV and visible light irradiation, Fe is converted to Fe by a ligand-metal-charge transfer (LMCT) step. 3+ Reduction to Fe 2+ These Fe 3+ -Carboxylic acid complexes have higher quantum yields than Fe(OH) 2+ The quantum yield of Fenton reaction can maintain good degradation efficiency even at higher pH.

[0031] (4) The bimetallic carbon nanocube-doped alginate hydrogel prepared by the present invention has good Fenton performance under various environments and has a good degradation effect on various types of pollutants.

[0032] (5) The bimetallic carbon nanocube-doped alginate hydrogel prepared by the present invention is relatively stable and has good Fenton performance after 5 cycles.

[0033] (6) Compared with the prior art, the present invention has simple process, environmentally friendly raw materials, strong Fenton performance and stability, is easy to recycle, and is suitable for the field of sewage treatment. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.

[0035] Figure 1 This is a scanning electron microscope photograph of the Cu-Co-CNC prepared in Example 1 of the present invention;

[0036] Figure 2 This is a scanning electron microscope photograph of the bimetallic carbon nanocube-doped alginate hydrogel prepared in Example 1 of the present invention;

[0037] Figure 3 This is a scanning electron microscope photograph of the alginate hydrogel prepared in Comparative Example 1 of the present invention;

[0038] Figure 4 The surface area and pore size analysis of the hydrogels prepared in Example 1 and Comparative Example 1 of the present invention; wherein (a) is a surface area test comparison diagram of the hydrogels prepared in Example 1 and Comparative Example 1; (b) is a pore size analysis diagram of the hydrogels prepared in Example 1 and Comparative Example 1;

[0039] Figure 5 The degradation efficiency of malachite green by the hydrogels prepared in Example 1 and Comparative Example 1 of the present invention;

[0040] Figure 6 The degradation efficiency of malachite green by the hydrogel prepared in Example 1 and Examples 2 to 3 of the present invention;

[0041] Figure 7 The degradation efficiency of the hydrogels prepared in Examples 1 and 4-5 of the present invention on different types of organic pollutants;

[0042] Figure 8 The degradation efficiency of malachite green by the hydrogels prepared in Examples 1 and 6 to 7 of the present invention;

[0043] Fig. 9 The degradation efficiency of malachite green by the hydrogels prepared in Examples 1 and 8 of the present invention under the influence of different anions;

[0044] Fig.10 The number of cycles of malachite green degradation by the hydrogel prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0045] It should be noted that the following detailed descriptions are exemplary and are intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used in the present invention have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.

[0046] The present invention will be further described in detail below in conjunction with specific embodiments. It should be noted that the specific embodiments are intended to explain the present invention rather than to limit it.

[0047] Example 1 :This embodiment provides a bimetallic carbon nanocube-doped alginate hydrogel and a preparation method thereof, which specifically comprises the following steps:

[0048] (1) 2 g of sodium alginate was dissolved in 100 g of deionized water, and the mixture was stirred at 25° C. for 2 h to form a uniform sol. The mixture was vacuum degassed at 60° C. (pressure was −25 KPa) to obtain a sodium alginate aqueous solution with a mass percent concentration of 2%.

[0049] (2) Add 0.4 mol of copper nitrate and 0.6 mol of cobalt nitrate into 100 mL of deionized water and stir well.

[0050] (3) Add 22.7 g of dimethylimidazole to 300 mL of deionized water and stir well.

[0051] (4) Slowly adding the copper nitrate and cobalt nitrate aqueous solutions of step (2) to the dimethylimidazole aqueous solution of step (3) to carry out stirring reaction, and then standing for 12 hours to obtain a mixed solution.

[0052] (5) Centrifuging the mixed solution in step (4) to obtain Cu-Co-ZIF powder.

[0053] (6) Place step (5) in a tubular furnace and perform carbonization in a nitrogen environment at a heating rate of 2°C / min at 600°C for 2 h to obtain Cu-Co-CNC powder.

[0054] (7) Add 1 g of the powder obtained in step (6) into the sodium alginate aqueous solution obtained in step (1) and stir evenly.

[0055] (8) The mixed solution obtained in step (7) is dripped dropwise into a 5% by mass concentration of ferric chloride aqueous solution, allowed to stand for 12 hours, and rinsed with deionized water to obtain a bimetallic carbon nanocube-doped alginate hydrogel.

[0056] (9) Place 1 g of the hydrogel obtained in step (8) in a malachite green aqueous solution (100 mL, 10 mg / L), adjust the pH to 7, and let it stand for 20 min until the adsorption reaches saturation.

[0057] (10) Place 0.005 mol of H2O2 under sunlight, take a small amount of sample at regular intervals, and measure the change in concentration.

[0058] like Figure 1 As shown, the Cu-Co-ZIF material still has a cubic structure after carbonization;

[0059] like Figures 2-3 As shown, the bimetallic carbon nanocube-doped alginate hydrogel prepared by the present invention has a porous morphology compared to alginate hydrogel, which provides more active sites for Fenton reaction;

[0060] like Figure 4 As shown, the BET test can further verify this result:

[0061] Figure 4 Figure (a) shows that although the surface area of ​​the bimetallic carbon nanocube-doped alginate hydrogel prepared by the present invention is slightly reduced, the hysteresis curve type changes from the H3 type with uneven pore size to the H2 type hysteresis curve with relatively uniform pore size;

[0062] Figure 4 Figure (b) shows that the pore size distribution results of the bimetallic carbon nanocube-doped alginate hydrogel prepared by the present invention confirm the coexistence of micropores and mesopores.

[0063] Compared with Comparative Example 1, the bimetallic carbon nanocube-doped alginate hydrogel prepared in the present invention has a larger pore volume and more abundant micropores and mesopores, which can provide a larger surface to provide active sites, thereby improving the catalytic activity.

[0064] Example 2 :This embodiment provides a bimetallic carbon nanocube doped alginate hydrogel and a preparation method thereof

[0065] (1) 2 g of sodium alginate was dissolved in 100 g of deionized water, and the mixture was stirred at 25° C. for 2 h to form a uniform sol. The mixture was vacuum degassed at 60° C. (pressure was −25 KPa) to obtain a sodium alginate aqueous solution with a mass percent concentration of 2%.

[0066] (2) Add 0.3 mol of copper nitrate and 0.7 mol of cobalt nitrate into 100 mL of deionized water and stir well.

[0067] (3) Add 22.7 g of dimethylimidazole into 300 mL of deionized water and stir well.

[0068] (4) Slowly adding the copper nitrate and cobalt nitrate aqueous solutions of step (2) into the dimethylimidazole aqueous solution of step (2) to carry out stirring reaction, and standing for 12 hours to obtain a mixed solution.

[0069] (5) Centrifuging the mixed solution in step (4) to obtain Cu-Co-ZIF powder.

[0070] (6) Place step (5) in a tubular furnace and perform carbonization in a nitrogen environment at a heating rate of 2°C / min at 600°C for 2 h to obtain Cu-Co-CNC powder.

[0071] (7) Add 1 g of the powder obtained in step (6) into the sodium alginate aqueous solution obtained in step (1) and stir evenly.

[0072] (8) The mixed solution obtained in step (7) is dripped dropwise into a 5% by mass concentration of ferric chloride aqueous solution, allowed to stand for 12 hours, and rinsed with deionized water to obtain a bimetallic carbon nanocube-doped alginate hydrogel.

[0073] (9) Place 1 g of the hydrogel obtained in step (8) in a malachite green aqueous solution (100 mL, 10 mg / L), adjust the pH to 7, and let it stand for 20 min until the adsorption reaches saturation.

[0074] (10) Place 0.005 mol of H2O2 under sunlight, take a small amount of sample at regular intervals, and measure the change in concentration.

[0075] Example 3 :This embodiment provides a bimetallic carbon nanocube doped alginate hydrogel and a preparation method thereof

[0076] (1) 2 g of sodium alginate was dissolved in 100 g of deionized water, and the mixture was stirred at 25° C. for 2 h to form a uniform sol. The mixture was vacuum degassed at 60° C. (pressure was −25 KPa) to obtain a sodium alginate aqueous solution with a mass percent concentration of 2%.

[0077] (2) Add 0.5 mol of copper nitrate and 0.5 mol of cobalt nitrate into 100 mL of deionized water and stir well.

[0078] (3) Add 22.7 g of dimethylimidazole into 300 mL of deionized water and stir well.

[0079] (4) Slowly adding the copper nitrate and cobalt nitrate aqueous solutions of step (2) into the dimethylimidazole aqueous solution of step (2) to carry out stirring reaction, and standing for 12 hours to obtain a mixed solution.

[0080] (5) The mixed solution in step (4) is centrifuged / filtered to obtain Cu-Co-ZIF powder.

[0081] (6) Place step (5) in a tubular furnace and perform carbonization in a nitrogen environment at a heating rate of 2°C / min at 600°C for 2 h to obtain Cu-Co-CNC powder.

[0082] (7) Add 1 g of the powder obtained in step (6) into the sodium alginate aqueous solution obtained in step (1) and stir evenly.

[0083] (8) The mixed solution obtained in step (7) is dripped dropwise into a 5% by mass concentration of ferric chloride aqueous solution, allowed to stand for 12 hours, and rinsed with deionized water to obtain a bimetallic carbon nanocube-doped alginate hydrogel.

[0084] (9) Place 1 g of the hydrogel obtained in step (8) in a malachite green (MG) aqueous solution (100 mL, 10 mg / L), adjust the pH to 7, and let it stand for 20 min until the adsorption reaches saturation.

[0085] (10) Place 0.005 mol of H2O2 under sunlight, take a small amount of sample at regular intervals, and measure the change in concentration.

[0086] Example 4 :This embodiment provides a bimetallic carbon nanocube doped alginate hydrogel and a preparation method thereof

[0087] (1) 2 g of sodium alginate was dissolved in 100 g of deionized water, and the mixture was stirred at 25° C. for 2 h to form a uniform sol. The mixture was vacuum degassed at 60° C. (pressure was −25 KPa) to obtain a sodium alginate aqueous solution with a mass percent concentration of 2%.

[0088] (2) Add 0.4 mol of copper nitrate and 0.6 mol of cobalt nitrate into 100 mL of deionized water and stir well.

[0089] (3) Add 22.7 g of dimethylimidazole into 300 mL of deionized water and stir well.

[0090] (4) Slowly adding the copper nitrate and cobalt nitrate aqueous solutions of step (2) to the dimethylimidazole aqueous solution of step (3) to carry out stirring reaction, and then standing for 12 hours to obtain a mixed solution.

[0091] (5) The mixed solution in step (4) is centrifuged / filtered to obtain Cu-Co-ZIF powder.

[0092] (6) Place step (5) in a tubular furnace and perform carbonization in a nitrogen environment at a heating rate of 2°C / min at 600°C for 2 h to obtain Cu-Co-CNC powder.

[0093] (7) Add 1 g of the powder obtained in step (6) into the sodium alginate aqueous solution obtained in step (1) and stir evenly.

[0094] (8) The mixed solution obtained in step (7) is dripped dropwise into a 5% by mass concentration of ferric chloride aqueous solution, allowed to stand for 12 hours, and rinsed with deionized water to obtain a bimetallic carbon nanocube-doped alginate hydrogel.

[0095] (9) 1 g of the hydrogel obtained in step (8) was placed in a rhodamine B (RHB) aqueous solution (100 mL, 5 mg / L), the pH was adjusted to 7, and the solution was allowed to stand for 20 min until adsorption reached saturation.

[0096] (10) Place 0.005 mol of H2O2 under sunlight, take a small amount of sample at regular intervals, and measure the change in concentration.

[0097] Example 5 :This embodiment provides a bimetallic carbon nanocube doped alginate hydrogel and a preparation method thereof

[0098] (1) 2 g of sodium alginate was dissolved in 100 g of deionized water, and the mixture was stirred at 25° C. for 2 h to form a uniform sol. The mixture was vacuum degassed at 60° C. (pressure was −25 KPa) to obtain a sodium alginate aqueous solution with a mass percent concentration of 2%.

[0099] (2) Add 0.4 mol of copper nitrate and 0.6 mol of cobalt nitrate into 100 mL of deionized water and stir well.

[0100] (3) Add 22.7 g of dimethylimidazole to 300 mL of deionized water and stir well.

[0101] (4) Slowly adding the copper nitrate and cobalt nitrate aqueous solutions of step (2) to the dimethylimidazole aqueous solution of step (3) to carry out stirring reaction, and then standing for 12 hours to obtain a mixed solution.

[0102] (5) The mixed solution in step (4) is centrifuged / filtered to obtain Cu-Co-ZIF powder.

[0103] (6) Place step (5) in a tubular furnace and perform carbonization in a nitrogen environment at a heating rate of 2°C / min at 600°C for 2 h to obtain Cu-Co-CNC powder.

[0104] (7) Add 1 g of the powder obtained in step (6) into the sodium alginate aqueous solution obtained in step (1) and stir evenly.

[0105] (8) The mixed solution obtained in step (7) is dripped dropwise into a 5% by mass concentration of ferric chloride aqueous solution, allowed to stand for 12 hours, and rinsed with deionized water to obtain a bimetallic carbon nanocube-doped alginate hydrogel.

[0106] (9) Place 1 g of the hydrogel obtained in step (8) in a tetracycline (TC) aqueous solution (100 mL, 5 mg / L), adjust the pH to 7, and let it stand for 20 min until the adsorption reaches saturation.

[0107] (10) 0.005 mol of H2O2 was added under sunlight. A small amount of sample was taken at regular intervals and the change in concentration was measured.

[0108] Example 6 :This embodiment provides a bimetallic carbon nanocube doped alginate hydrogel and a preparation method thereof

[0109] (1) 2 g of sodium alginate was dissolved in 100 g of deionized water, and the mixture was stirred at 25° C. for 2 h to form a uniform sol. The mixture was vacuum degassed at 60° C. (pressure was −25 KPa) to obtain a sodium alginate aqueous solution with a mass percent concentration of 2%.

[0110] (2) Add 0.4 mol of copper nitrate and 0.6 mol of cobalt nitrate into 100 mL of deionized water and stir well.

[0111] (3) Add 22.7 g of dimethylimidazole to 300 mL of deionized water and stir well.

[0112] (4) Slowly adding the copper nitrate and cobalt nitrate aqueous solutions of step (2) to the dimethylimidazole aqueous solution of step (3) to carry out stirring reaction, and then standing for 12 hours to obtain a mixed solution.

[0113] (5) The mixed solution in step (4) is centrifuged / filtered to obtain Cu-Co-ZIF powder.

[0114] (6) Place step (5) in a tubular furnace and perform carbonization in a nitrogen environment at a heating rate of 2°C / min at 600°C for 2 h to obtain Cu-Co-CNC powder.

[0115] (7) Add 1 g of the powder obtained in step (6) into the sodium alginate aqueous solution obtained in step (1) and stir evenly.

[0116] (8) The mixed solution obtained in step (7) is dripped dropwise into a 5% by mass concentration of ferric chloride aqueous solution, allowed to stand for 12 hours, and rinsed with deionized water to obtain a bimetallic carbon nanocube-doped alginate hydrogel.

[0117] (9) Place 1 g of the hydrogel obtained in step (8) in a malachite green aqueous solution (100 mL, 10 mg / L), adjust the pH to 5, and let it stand for 20 min until the adsorption reaches saturation.

[0118] (10) Place 0.005 mol of H2O2 under sunlight, take a small amount of sample at regular intervals, and measure the change in concentration.

[0119] Example 7 :This embodiment provides a bimetallic carbon nanocube doped alginate hydrogel and a preparation method thereof

[0120] (1) 2 g of sodium alginate was dissolved in 100 g of deionized water, and the mixture was stirred at 25° C. for 2 h to form a uniform sol. The mixture was vacuum degassed at 60° C. (pressure was −25 KPa) to obtain a sodium alginate aqueous solution with a mass percent concentration of 2%.

[0121] (2) Add 0.4 mol of copper nitrate and 0.6 mol of cobalt nitrate into 100 mL of deionized water and stir well.

[0122] (3) Add 22.7 g of dimethylimidazole into 300 mL of deionized water and stir well.

[0123] (4) Slowly adding the copper nitrate and cobalt nitrate aqueous solutions of step (2) to the dimethylimidazole aqueous solution of step (3) to carry out stirring reaction, and then standing for 12 hours to obtain a mixed solution.

[0124] (5) The mixed solution in step (4) is centrifuged / filtered to obtain Cu-Co-ZIF powder.

[0125] (6) Place step (5) in a tubular furnace and perform carbonization in a nitrogen environment at a heating rate of 2°C / min at 600°C for 2 h to obtain Cu-Co-CNC powder.

[0126] (7) Add 1 g of the powder obtained in step (6) into the sodium alginate aqueous solution obtained in step (1) and stir evenly.

[0127] (8) The mixed solution obtained in step (7) is dripped dropwise into a 5% by mass concentration of ferric chloride aqueous solution, allowed to stand for 12 hours, and rinsed with deionized water to obtain a bimetallic carbon nanocube-doped alginate hydrogel.

[0128] (9) Place 1 g of the hydrogel obtained in step (8) in a malachite green aqueous solution (100 mL, 10 mg / L), adjust the pH to 3, and let it stand for 20 min until the adsorption reaches saturation.

[0129] (10) Place 0.005 mol of H2O2 under sunlight, take a small amount of sample at regular intervals, and measure the change in concentration.

[0130] Example 8 :This embodiment provides a bimetallic carbon nanocube doped alginate hydrogel and a preparation method thereof

[0131] (1) 2 g of sodium alginate was dissolved in 100 g of deionized water, and the mixture was stirred at 25° C. for 2 h to form a uniform sol. The mixture was vacuum degassed at 60° C. (pressure was −25 KPa) to obtain a sodium alginate aqueous solution with a mass percent concentration of 2%.

[0132] (2) Add 0.4 mol of copper nitrate and 0.6 mol of cobalt nitrate into 100 mL of deionized water and stir well.

[0133] (3) Add 22.7 g of dimethylimidazole to 300 mL of deionized water and stir well.

[0134] (4) Slowly adding the copper nitrate and cobalt nitrate aqueous solutions of step (2) to the dimethylimidazole aqueous solution of step (3) to carry out stirring reaction, and then standing for 12 hours to obtain a mixed solution.

[0135] (5) Centrifuging the mixed solution in step (4) to obtain Cu-Co-ZIF powder.

[0136] (6) Place step (5) in a tubular furnace and perform carbonization in a nitrogen environment at a heating rate of 2°C / min at 600°C for 2 h to obtain Cu-Co-CNC powder.

[0137] (7) Add 1 g of the powder obtained in step (6) into the sodium alginate aqueous solution obtained in step (1) and stir evenly.

[0138] (8) The mixed solution obtained in step (7) is dripped dropwise into a 5% by mass concentration of ferric chloride aqueous solution, allowed to stand for 12 hours, and rinsed with deionized water to obtain a bimetallic carbon nanocube-doped alginate hydrogel.

[0139] (9) Place 1 g of the hydrogel obtained in step (8) in a malachite green aqueous solution (100 mL, 10 mg / L) and add a small amount of anions (such as PO4 2- , Cl - 、SO4 2- 、HCO3 -), adjust the pH to 7, and let it stand for 20 minutes to wait for the adsorption to reach saturation.

[0140] (10) Place 0.005 mol of H2O2 under sunlight, take a small amount of sample at regular intervals, and measure the change in concentration.

[0141] Comparative Example 1 :This embodiment provides an alginate hydrogel and a preparation method

[0142] (1) 2 g of sodium alginate was dissolved in 100 g of deionized water, and the mixture was stirred at 25° C. for 2 h to form a uniform sol. The mixture was vacuum degassed at 60° C. (pressure was −25 KPa) to obtain a sodium alginate aqueous solution with a mass percent concentration of 2%.

[0143] (2) The sodium alginate aqueous solution in step (1) is dripped dropwise into a 5% by mass ferric chloride aqueous solution, allowed to stand for 12 hours, and rinsed with deionized water to obtain an alginate hydrogel.

[0144] (3) Place 1 g of the hydrogel obtained in step (2) in a malachite green aqueous solution (100 mL, 10 mg / L), adjust the pH to 7, and let it stand for 20 min until the adsorption reaches saturation.

[0145] (4) Place 0.005 mol of H2O2 under sunlight, take a small amount of sample at regular intervals, and measure the change in concentration.

[0146] Experimental Example 1 :

[0147] This experimental example analyzes the concentration of the solution after degradation of the hydrogels prepared in Examples 1 to 8 and Comparative Example 1:

[0148] (1) From the test results of Examples 1 and 2, it can be seen that Figure 5 As shown, compared with Comparative Example 1, the addition of carbon nanocubes in Example 1 increased the removal rate of malachite green by the hydrogel from 59.795% to 80.830% within 60 minutes.

[0149] (2) From the test results of Examples 1 and 2-3, it can be seen that Figure 6 As shown, compared with Example 2 and Example 3, when the addition ratio of copper nitrate and cobalt nitrate in Example 1 is 4:6, the degradation efficiency is optimal, which may be related to the binding ability of Cu, Co and dimethylimidazole.

[0150] (3) From the test results of Examples 1 and 4-5, it can be seen that Figure 7 As shown, the hydrogel has good degradation ability for various types of pollutants (such as MB, TC, and RH B) and has strong applicability.

[0151] (4) From the test results of Examples 1 and 6-7, it can be seen that Figure 8 As shown, as the pH gradually decreases, the degradation efficiency gradually increases. This is because the Fenton reaction is an acidic reaction. However, it can also be seen that the hydrogel also has a good degradation efficiency under neutral conditions.

[0152] (5) From the test results of Example 1 and Example 8, it can be seen that Fig. 9 As shown, the hydrogel prepared by the present invention has good degradation performance under the influence of different anions.

[0153] (6) Fig.10 As shown, by performing multiple degradation experiments on the hydrogel of Example 1, it was found that the hydrogel prepared in the present application still had good degradation performance and good stability after 5 cycles.

[0154] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A bimetallic carbon nanocube-doped alginate hydrogel, characterized in that: The alginate hydrogel comprises a sodium alginate skeleton, Cu-Co-carbon nanocubes distributed on the sodium alginate skeleton, and Fe 3+ .

2. A method for preparing the bimetallic carbon nanocube-doped alginate hydrogel as claimed in claim 1, characterized in that: The steps include: S1, carbonizing Cu-Co-ZIF to obtain Cu-Co-carbon nanocubes; S2, add Cu-Co-carbon nanocubes to the sodium alginate aqueous solution, and add the mixture to the Fe-containing 3+ in a coagulation bath to obtain the product.

3. The preparation method according to claim 2, characterized in that: In step S1, the specific preparation steps of the Cu-Co-ZIF are: adding an aqueous solution mixed with copper salt and cobalt salt to a dimethylimidazole aqueous solution, and the mixed solution is allowed to stand for reaction to obtain the Cu-Co-ZIF; Wherein, the mass fraction of the dimethylimidazole aqueous solution is 0.07% to 0.08%; the molar ratio of the copper salt to the cobalt salt is 3 to 5:5 to 7, preferably 4:

6.

4. The preparation method according to claim 3, characterized in that: The copper salt is selected from one or more of copper nitrate, copper sulfate and copper chloride, and the cobalt salt is selected from one or more of cobalt nitrate, cobalt sulfate and cobalt chloride; preferably, the copper salt is copper nitrate, and the cobalt salt is cobalt nitrate.

5. The preparation method according to claim 3, characterized in that: The standing time is 12 to 16 hours; preferably, the mixed solution after the standing reaction is centrifuged to obtain Cu-Co-ZIF.

6. The preparation method according to claim 2, characterized in that: In step S1, the reaction conditions of the carbonization treatment are: in an inert environment, heating to 450-600°C at a heating rate of 1-3°C / min, and keeping warm for 1-3h; preferably, heating to 600°C at a heating rate of 2°C / min, and keeping warm for 2h.

7. The preparation method according to claim 2, characterized in that: In step S2, the sodium alginate is extracted from marine biomass resources, and the marine biomass resources are selected from one or more of brown algae, sargassum, and agar; preferably, the mass concentration of the sodium alginate aqueous solution is 2.0% to 3.0%.

8. The preparation method according to claim 2, characterized in that: In step S2, the sodium alginate aqueous solution is prepared by dissolving sodium alginate in deionized water, stirring the solution to form a uniform sol, and then performing a degassing treatment at 60° C. under vacuum; Preferably, the stirring reaction time is 1 to 3 hours, the temperature is 20°C to 30°C, and the stirring rate is 500 to 700 r / min; the temperature of the vacuum degassing treatment is 50 to 70°C, and the pressure is -20 to -30 KPa.

9. The preparation method according to claim 2, characterized in that: In step S2, the mass ratio of the Cu-Co-carbon nanocubes to the sodium alginate aqueous solution is 0.8-1.2:1.5-2.5; preferably 1:2; Preferably, the Fe-containing 3+ The coagulation bath is an FeCl3 aqueous solution, the mass fraction of the FeCl3 aqueous solution is 4% to 6%, and the reaction time is 8 to 15 hours.

10. Application of bimetallic carbon nanocube-doped alginate hydrogel prepared by the preparation method according to any one of claims 2 to 9 in the field of sewage treatment; Preferably, the organic pollutants in the sewage treatment include malachite green, rhodamine B, and tetracycline; Further preferably, the method for degrading organic pollutants comprises: Bimetallic carbon nanocube-doped alginate hydrogel is added to wastewater containing organic pollutants, and the pH is adjusted to 3-7. After the hydrogel is completely dispersed and adsorption equilibrium is reached, it reacts with hydrogen peroxide under visible light to photocatalytically degrade the organic pollutants.